Analisis Motivasi Belajar Internal Siswa pada Mata Pelajaran Biologi di Kota Semarang - Deasy Lutviana; Miswari miswari; Erna Wijayanti (Center of Education Journal (CEJou), 2021)
The aim of the research is to analyze students' internal learning motivation. The samples of this research are 117 students from the X and XI Class of Science Program. This research used a descriptive approach, and the sampling technique in this research is cluster random sampling. The data was collected from questionnaires, interviews, and observation. The questionnaire was analyzed using descriptive quantitatively while interview and observation were analyzed using qualitatively. The qualitative study's research concluded that students' internal learning motivation at class X MIPA 76,36% with high criteria and class XI MIPA 74,90% with middle criteria, obtain an average 75,63% with high criteria.